PLEISTOCENE PALYNOLOGY OF EAST JAVA - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2006)
This study is a part of geological investigation on Pleistocene sediment in East Java in order to evaluate hydrocarbon potential within this sediment of this area. The area of study is located in the on-shore East Java (Figure 1). It is financially supported by the oil company as this is commercial work done by LEMIGAS Exploration Department. Therefore, data used in this paper will be incompletely presented as they are confidential. The name of the studied wells and their precise locations are hided in this paper. Data used in this study derives from three wells namely R, S and T. Three different disciplines are applied in this study including palynology, micropaleontology and nannoplankton analyses which are useful for crosschecking purposes. Apparently, the integration of these analyses gains accurate interpretation of stratigraphy and depositional environment. The area of study is in East Java Basin which can be classified as a classical back-arc basin. During Pleistocene, the area of study was marked by regional uplift and the cessation of open marine sedimentation (LEMIGAS, 2005). Therefore Pleistocene age was dominated by non-marine deposition. Generally, this type of sediment is separated from the underlying layer by an unconformity (LEMIGAS, 2005). Most Pleistocene sediment consists of volcanoclastic as a result of volcanic activity which related to uplifting period. It is possible that volcanic activity was responsible for the burning of grass as indicated by the occurrence of charred Gramineae cuticles. The previous investigations on Pleistocene sediment showed the domination of grass pollen of Monoporites annulatus which suggested the expansion of dry climate during Pleistocene glacial maxima. The pollen diagram from Lombok Ridge produced by van der Kaas (1991a) proves the domination of Gramineae pollen during Pleistocene (Figure 2). The period of dry climate (glacial climate) is characterised by abundant Gramineae pollen, whilst the period of wetter climate (interglacial climate) is indicated byÂ an increase of coastal and mangrove palynomorphs, but greatly reduced frequencies of Graminaae pollen (Morley, 2000). In addition, Rahardjo et al. (1994) referred to the high abundance of Monoporites annulatus to propose Pleistocene pollen zone of M. annulatus (Figure 3).